Quantifying Li-content for compositional tailoring of lithium ferrite ceramics. Issue 8 (July 2023) - Granados-Miralles, C.; Serrano, A.; Prieto, P.; Guzmán-Mínguez, J.; Prieto, J.E.; Friedel, A.M.; García-Martín, E.; Fernández, J.F.; Quesada, A.
Abstract: Owing to their multiple applications, lithium ferrites are relevant materials for several emerging technologies. For instance, LiFeO2 has been spotted as an alternative cathode material in Li-ion batteries, while LiFe5 O8 is the lowest damping ferrite, holding promise in the field of spintronics. The Li-content in lithium ferrites has been shown to greatly affect the physical properties, and in turn, the performance of functional devices based on these materials. Despite this, lithium content is rarely accurately quantified, as a result of the low number of electrons in Li hindering its identification by means of routine materials characterization methods. In the present work, magnetic lithium ferrite powders with Li:Fe ratios of 1:1, 1:3 and 1:5 have been synthesized, successfully obtaining phase-pure materials (LiFeO2 and LiFe5 O8 ), as well as a controlled mixture of both phases. The powders have been compacted and subsequently sintered by thermal treatment ( T max = 1100 °C) to fabricate dense pellets which preserve the original Li:Fe ratios. Li-content on both powders and pellets has been determined by two independent methods: (i) Rutherford backscattering spectroscopy combined with nuclear reaction analysis and (ii) Rietveld analysis of powder X-ray diffraction data. With good agreement between both techniques, it has been confirmed that the Li:Fe ratios employed in the synthesis are maintained in the sintered ceramics. The same conclusion is drawn from spatially-resolved confocal Raman microscopy experiments on regions of a few microns. Field emission scanning electron microscopy has evidenced the substantial grain growth taking place during the sintering process – mean particle sizes rise from ≈ 600 nm in the powders up to 3.8(6) µm for dense LiFeO2 and 10(2) µm for LiFe5 O8 ceramics. Additionally, microstructural analysis has revealed trapped pores inside the grains of the sintered ceramics, suggesting that grain boundary mobility is governed by surface diffusion. Vibrating sample magnetometry on the ceramic samples has confirmed the expected soft ferrimagnetic behavior of LiFe5 O8 (with M s = 61.5(1) Am 2 /kg) and the paramagnetic character of LiFeO2 at room temperature. A density of 92.7(6)% is measured for the ceramics, ensuring the mechanical integrity required for both their direct utilization in bulk shape and their use as targets for thin-film deposition.